Library and information science in developing countries contemporary issues - Tella, A. (Adeyinka), 1972-; Issa, A. O. (Abdulwahaab Olanrewaju), 1967-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book explores the relationship between global technology development and the impact of new technologies on library practice, library education, and information science"--Provided by publisher.
13. Demystifying digital scholarship / Stephen M. Mutula -- 14. Establishing the digital library: don't ignore the library standards and don't forget the training needed / Alan Hopkinson -- 15. A review of eGovernment services in Nigeria / Gbola Olasina -- 16. Digital libraries: their challenges and issues in the perspectives of developing countries like India / N. Swaminathan -- 17. Information flow and democratic governance: an analysis of the African experience / F. A. Aremu and H. T. Saka -- 18. Librarians, records managers, and e-government / Cathrine T. Nengomasha -- 19. Information services provision to persons with visual impairment in Nigeria: the salient issues / Niran Adetoro -- 20. Organisation of information and the information retrieval system / Edeama O. Onwuchekwa -- 21. Social media in library and information centres / Ayodele John Alonge -- 22. Bibliometric analysis of DESIDOC Journal of library & information technology / S. Thanuskodi -- 23. Cataloguing and classification of library resources in the 21st century / Lydia O. Adedibu, Evelyn O. Akinboro and Titilola A. B. Abdussalam.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed November 19, 2011).
Keywords: Library science -- Developing countries; Information science -- Developing countries; Libraries -- Developing countries; Library education -- Developing countries; Career progression of library professionals; Curriculum delivery; Database management; Digital libraries; Digital scholarship; E-records management; Funding of library school programs; Metadata; Staffing; Electronic books